A Two-DOF Fast Tool Servo for Optical Freeform Surfaces Diamond Turning. (22nd October 2014) - Liu, Qiang; Zhou, Xiaoqin; Xu, Pengzi; Zhang, Xu
Abstract : Fast tool servo (FTS) technology is considered as the most popular technology to fabricate freeform optical lenses and micro- and nano-structured surfaces. Aiming at the disadvantages of existing single DOF FTS systems, this paper described a two-DOF FTS. Cross shape flexure hinges are designed as the guide mechanism, and two voice coil motors (VCMs) are selected to drive the tool motion. The FTS offline performance is tested, and the following error is about less than 0.1 μ m; the motion resolution is 0.05 μ m. A sinusoidal surface is machined to verify the cutting performance of the novel FTS, and the surface roughness is Ra 27 nm. The test results show that the two-DOF FTS system works well on the fabrication of optical freeform surfaces.